2004
DOI: 10.1111/j.0953-816x.2004.03308.x
|View full text |Cite
|
Sign up to set email alerts
|

Comparative analysis of CNS populations in knockout mice with altered growth hormone responsiveness

Abstract: Recently we have shown that growth hormone (GH) inhibits neuronal differentiation and that this process is blocked by suppressor of cytokine signalling-2 (SOCS2). Here we examine several cortical and subcortical neuronal populations in GH hyper-responsive SOCS2 null (-/-) mice and GH non-responsive GH receptor null (GHR-/-) mice. While SOCS2-/- mice showed a 30% decrease in density of NeuN positive neurons in cortex compared to wildtype, GHR-/- mice showed a 25% increase even though brain size was decreased. I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
56
0

Year Published

2008
2008
2012
2012

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 73 publications
(58 citation statements)
references
References 51 publications
2
56
0
Order By: Relevance
“…8,11,12,36,37 In regard to the findings with GH, our data agree with a previous report demonstrating reduced brain size and sparser dendritic arborization in GH receptor-deficient (GHR À/À ) mice. 38 Neurite initiation and sprouting were significantly increased in Stat5 À/À neurons as compared to Stat5 þ / þ cells, suggesting that Stat5 activity might negatively regulate neurite outgrowth. Therefore, we cannot exclude the possibility that the increased baseline of sprouting in Stat5 À/À neurons might have masked the stimulatory effects of EPO and GH.…”
Section: Discussionmentioning
confidence: 96%
“…8,11,12,36,37 In regard to the findings with GH, our data agree with a previous report demonstrating reduced brain size and sparser dendritic arborization in GH receptor-deficient (GHR À/À ) mice. 38 Neurite initiation and sprouting were significantly increased in Stat5 À/À neurons as compared to Stat5 þ / þ cells, suggesting that Stat5 activity might negatively regulate neurite outgrowth. Therefore, we cannot exclude the possibility that the increased baseline of sprouting in Stat5 À/À neurons might have masked the stimulatory effects of EPO and GH.…”
Section: Discussionmentioning
confidence: 96%
“…In addition, SOCS2 plays a role in the nervous system [20][21][22] and the immune response [23] and might participate in certain cancers [24][25][26]. To date, little is known about the impact of SOCS2 on pancreatic physiology.…”
Section: Introductionmentioning
confidence: 99%
“…Although our investigation was targeting adult effects of local GH, it has to be kept in mind that the bGH-Tg came into effect in the early postnatal life when GFAP started to become expressed. As previous TG models that either increase or decrease GH signalling affect astrocyte numbers (Turnley et al 2002, Ransome et al 2004, at least in the cerebral cortex, it is plausible that astrocyte numbers may have slowly accumulated during the development. Such a slow accumulation may not have been detected in our assays of proliferating cells.…”
Section: Discussionmentioning
confidence: 90%
“…Two previous studies using TG models affecting GH signalling in the developing and adult brain have demonstrated an influence on the number of astrocytes in the cerebral cortex (Turnley et al 2002, Ransome et al 2004. Specifically, disruption of GH signalling, via GH receptor (GHR K/K ), decreased astrocyte numbers and increased neuron numbers (Ransome et al 2004), while increasing GH signalling via disrupting the suppressor of cytokine signalling 2 (SOCS2) decreased neuron numbers and presumably increased astrocyte numbers (Turnley et al 2002). Neither from these studies nor from our previous studies using glial fibrillary acidic protein (GFAP)-induced bGH-Tg, is it known whether hippocampal function is affected, as hippocampus-related parameters were not investigated.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation